Cross-Regime Evidence of Macroeconomic Rationality - Kormendi, Roger C.; Meguire, Philip G. (Journal of Political Economy, 1984)
Rational expectations macromodels predict that the short-run effects of monetary shocks on real output (X) should be negatively related across policy regimes to the variability of such shocks. This paper presents cross-regime tests of this and related propositions based on a sample of 47 countries. The within-regime estimates reveal a consistent pattern of positive short-run real output effects, with neutrality of money holding in the long run. The cross-regime tests show that X is negatively related to the variance of monetary shocks, positively related to the variance of real output shocks, negatively related to the variance of velocity shocks, and unrelated to either the mean or variance of anticipated money growth.